Unraveling the nexus of NAD+ metabolism and diabetic kidney disease: insights from murine models and human data - Yang, Sisi; Gong, Weiyuan; Wang, Yujia; Hao, Chuanming; Guan, Yi (Frontiers in Endocrinology, 2024)
Background Nicotinamide adenine dinucleotide (NAD+) is a critical coenzyme involved in kidney disease, yet its regulation in diabetic kidney disease (DKD) remains inadequately understood. Objective Therefore, we investigated the changes of NAD+ levels in DKD and the underlying mechanism. Methods Alternations of NAD+ levels and its biosynthesis enzymes were detected in kidneys from streptozotocin-induced diabetic mouse model by real-time PCR and immunoblot. The distribution of NAD+ de novo synthetic enzymes was explored via immunohistochemical study. NAD+ de novo synthetic metabolite was measured by LC-MS. Human data from NephroSeq were analyzed to verify our findings. Results The study showed that NAD+ levels were decreased in diabetic kidneys. Both mRNA and protein levels of kynurenine 3-monooxygenase (KMO) in NAD+ de novo synthesis pathway were decreased, while NAD+ synthetic enzymes in salvage pathway and NAD+ consuming enzymes remained unchanged. Further analysis of human data suggested KMO, primarily expressed in the proximal tubules shown by our immunohistochemical staining, was consistently downregulated in human diabetic kidneys. Conclusion Our study demonstrated KMO of NAD+ de novo synthesis pathway was decreased in diabetic kidney and might be responsible for NAD+ reduction in diabetic kidneys, offering valuable insights into complex regulatory mechanisms of NAD+ in DKD.